Short-Circuited Stub-Embedded Ring Resonator and its Application in Diplexer - Baoping Ren; Chenfei Le; Xuehui Guan; Zhewang Ma (IEEE Access, 2019)
Two types of short-circuited stub-embedded ring resonators (SERRs) are proposed in this paper. The resonant modes of the SERR can be designed by properly choosing the short-circuited point on the resonator. When the short-circuited point is set at the open-end of embedded-stub, type A resonator is realized and large frequency ratio of harmonic to fundamental frequency can be achieved. Simultaneously, wide stopband can be realized. When the short-circuited point is set at the loop portion of SERR, type B resonator is realized and low frequency ratio of harmonic to fundamental frequency can be achieved. These characteristics of the resonators type A and type B are explored and combined in a diplexer with common resonator part. Each channel of the diplexer are constructed by using the type A resonators for wide stopband, and then combined via a type B resonator for designated frequencies. A third-order diplexer operating at 3.45/5.8 GHz for fifth generation of mobile communications (5G) and wireless local area networks (WLAN) is designed, fabricated, and measured. Measured results agree well with the simulated ones, which confirms the proposed design methodology.